Social Networks and Health Inequalities A New Perspective for Research - Klärner, Andreas; Gamper, Markus; Keim-Klärner, Sylvia; Moor, Irene; von der Lippe, Holger; Vonneilich, Nico (Springer Nature, 2022)
This open access book applies insights from the network perspective in health research to explain the reproduction of health inequalities. It discusses the extant literature in this field that strongly correlates differences in social status with health behaviours and outcomes, and add to this literature by providing a coherent theoretical explanation for the causes of these health inequalities. It also shows that much research is needed on the precise factors and the social and socio-psychological mechanisms that are at play in creating and cementing social inequalities in health behaviours. While social support and social relations have received considerable attention within social and behavioural science research on health inequalities, this book considers the whole network of interpersonal relations, structures and influence mechanisms. This is the perspective of the social network analytical approach which has recently gained much attention in health research. The chapters of this book cover state-of-the-art research, open research questions, and perspectives for future research. The book provides network analyses on health inequalities from the perspective of sociology, psychology, and public health and is of interest to a wide range of scholars, students and practitioners trying to understand how health inequalities are reproduced across generations.